Changes in mountain vascular plants of the ‘Jar rzeki Raduni’ nature reserve (Poland) within the last 50 years - Zarzycki, Wojciech; Zarzycka, Magdalena; Gołębiewska, Joanna; Podsiedlik, Marek (Biodiversity: Research and Conservation, 2018)
‘Jar rzeki Raduni’ is a landscape nature reserve created in 1972, which covers an area of 74,26 ha. The reserve protects the Radunia river gorge in the moraine upland of the Kashubian Lake District. In past, the reserve was an object of numerous botanical studies, and it was distinguished by a large share of mountain species. The main aim of this research was to define the current state of mountain species of the studied area compared to historical data. The study was carried out in 2017. Eight mountain species were noted: Aconitum variegatum, Alnus incana, Bupleurum longifolium, Chaerophyllum hirsutum, Dryopteris expansa, Huperzia selago, Pleurospermum austriacum and Ribes alpinum. The occurrence of five species was not confirmed: Coeloglossum viride, Epipogium aphyllum, Melampyrum sylvaticum, Polygonatum verticillatum and Valeriana sambucifolia.